2006
DOI: 10.1143/jpsj.75.074803
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conductivity Measurement of DNA Double-Stranded Chains by “One-by-One” Cutting Method Using Atomic Force Microscopy

Abstract: We measured the electrical current-voltage characteristics of DNA in vacuum using fine electrodes with a gap of about 200 nm. It was found that the electrical resistance of DNA molecules between the fine electrodes had a large variation: from 7.8 M to values larger than 1 T. This was consistent with the controversial results given in previous reports. The temperature dependence of conductivity was explained well by the Arrhenius equation. In addition, the conductivity of a single molecule of doublestranded DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 22 publications
3
28
0
4
Order By: Relevance
“…Inomata et al [20] (II) for -DNA reported also pronounced strong temperature dependent conductance from 118 K to 265 K i.e. in a 147 K-wide temperature region.…”
Section: Comparison With Experiments and Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Inomata et al [20] (II) for -DNA reported also pronounced strong temperature dependent conductance from 118 K to 265 K i.e. in a 147 K-wide temperature region.…”
Section: Comparison With Experiments and Discussionmentioning
confidence: 92%
“…The use of simple Arrhenius-type formulae by others seems to be inadequate to account for important features of the actual transport mechanism and related information. This is probably the reason of a lack of a simultaneous interpretation of the experimental findings [4,18,20] which show a similar behavior of the conductivity in DNA at high temperatures.…”
Section: Comparison With Experiments and Discussionmentioning
confidence: 98%
See 3 more Smart Citations